Isolation and detection of urease genes in Ureaplasma urealyticum. - Willoughby, J J (1991)
Urease from ureaplasmas was purified by immunoaffinity chromatography, and the N-terminal amino acid sequence was determined for two of the three subunits. These sequences were used to design primers for a polymerase chain reaction (PCR) that amplified most of the gene coding for one of the subunits. By using a novel "PCR walking" technique, we synthesized almost the complete locus on two overlapping PCR products. We present here a partial nucleotide sequence of the urease locus from Ureaplasma urealyticum (serotype 8), which agrees with our N-terminal amino acid data but differs slightly from the sequence previously reported (A. Blanchard, Mol. Microbiol. 4:669-676, 1990). Also described are PCR primers, intended for diagnostic use, that amplify a sequence from all Ureaplasma strains tested but not from any other mycoplasmas or urease-positive bacteria.